2021
DOI: 10.3389/fcell.2021.696434
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapies for Progressive Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system characterized by demyelination and axonal degeneration. MS patients typically present with a relapsing-remitting (RR) disease course, manifesting as sporadic attacks of neurological symptoms including ataxia, fatigue, and sensory impairment. While there are several effective disease-modifying therapies able to address the inflammatory relapses associated with RRMS, most patients will inevitably advance to a progressive dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 274 publications
0
18
0
Order By: Relevance
“…In the context of non-active PMS, antigen-independent and compartmentalized chronic inflammation, shielded from therapeutic efforts, is plausible. The corollary to this hypothesis would be that even outside of common DMT, other anti-proliferative therapies might fail to provide meaningful clinical benefit to PMS ( 103 ), a logic that should guide hematopoietic stem cell transplants as well ( 104 ). Furthermore, if myeloid cells drive PMS, they probably do so in a stage-specific fashion; (1) BMC likely enter the CNS throughout active and non-active MS and are retained within the CNS; and (2) altered CNS-intrinsic myeloid cells, respond to BMC presence, at sites similar to the border of smoldering lesions.…”
Section: Innate Immunosenescence and Dmt Resistance In Pmsmentioning
confidence: 99%
“…In the context of non-active PMS, antigen-independent and compartmentalized chronic inflammation, shielded from therapeutic efforts, is plausible. The corollary to this hypothesis would be that even outside of common DMT, other anti-proliferative therapies might fail to provide meaningful clinical benefit to PMS ( 103 ), a logic that should guide hematopoietic stem cell transplants as well ( 104 ). Furthermore, if myeloid cells drive PMS, they probably do so in a stage-specific fashion; (1) BMC likely enter the CNS throughout active and non-active MS and are retained within the CNS; and (2) altered CNS-intrinsic myeloid cells, respond to BMC presence, at sites similar to the border of smoldering lesions.…”
Section: Innate Immunosenescence and Dmt Resistance In Pmsmentioning
confidence: 99%
“…These effects have been associated with reduced encephalitogenic T cells migration and activation and enhanced tolerance against myelin proteins [22]. About thirty clinical trials based on MSCs transplantation have been conducted so far in patients with MS [23], demonstrating safety and tolerability of the procedure and short-term benefits by inhibiting disease progression, especially in patients with previously active disease [24,25 ▪ ]. However, the outcome of the MESEMS study, which evaluated the activity of MSCs on MRI (gadolinium-enhancing lesions) and clinical (annualized relapse rate) surrogate markers of efficacy, do not support their use in patients with multiple sclerosis with ongoing inflammation [26 ▪▪ ].…”
Section: Preclinical and Clinical Trials Of Stem Cell-based Regenerat...mentioning
confidence: 99%
“…Due to the safety profile of MSCs when used for the treatment of other diseases—such as hematological malignancy, breast cancer, ischemic heart disease, and graft-versus-host disease—MSC-based therapy has been evoked for curing neurodegenerative diseases, including MS [ 81 , 82 ]. Most of the phase 1 or 2 clinical trials have employed autologous BM-MSCs or AD-MSCs, but allogeneic UC-MSCs and PMSCs have been also trialed [ 83 ]. A number of studies have demonstrated the feasibility and safety of intravenous (IV) or intrathecal (IT) administration, with disease stabilization and mitigation of clinical symptoms.…”
Section: Mesenchymal Stem (Stromal) Cells (Mscs)mentioning
confidence: 99%
“…However, a recent report on the MEsenchymal StEm cells for Multiple Sclerosis (MESEMS) study—a placebo-controlled, crossover phase 1/2 study [ 84 ]—failed to meet the primary efficacy endpoint represented by the reduction in the number of contrast-enhancing lesions detected by MRI at 24 weeks [ 85 ]. Other phase 2 and 3 clinical trials are either completed or ongoing [ 83 ]; however, it may be possible to assert at this stage of trial completion that MSCs are the main stem cell type sourced for clinical trials on MS to date.…”
Section: Mesenchymal Stem (Stromal) Cells (Mscs)mentioning
confidence: 99%